2020
DOI: 10.1038/s41598-020-75525-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac motion estimation from medical images: a regularisation framework applied on pairwise image registration displacement fields

Abstract: Accurate cardiac motion estimation from medical images such as ultrasound is important for clinical evaluation. We present a novel regularisation layer for cardiac motion estimation that will be applied after image registration and demonstrate its effectiveness. The regularisation utilises a spatio-temporal model of motion, b-splines of Fourier, to fit to displacement fields from pairwise image registration. In the process, it enforces spatial and temporal smoothness and consistency, cyclic nature of cardiac m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…A previous study approximating the heart as a linear tube has shown that the absence of red blood cells leads to a decrease in maximal wall shear stress of 2 to 3 times at 48 hpf [ 13 ]. Using a recently developed motion estimation algorithm [ 40 ], we were able to extract the position and motion of the cardiac wall (and blood cells in wild-type controls) in our movies of the beating heart and model wall shear stress in wild-type and gata1 mutants at 65 hpf. At this stage, when heartbeat is faster and stronger, we found that maximal wall shear stress at the AVC is approximately 3 to 4 times lower in gata1 mutants ( S10 Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study approximating the heart as a linear tube has shown that the absence of red blood cells leads to a decrease in maximal wall shear stress of 2 to 3 times at 48 hpf [ 13 ]. Using a recently developed motion estimation algorithm [ 40 ], we were able to extract the position and motion of the cardiac wall (and blood cells in wild-type controls) in our movies of the beating heart and model wall shear stress in wild-type and gata1 mutants at 65 hpf. At this stage, when heartbeat is faster and stronger, we found that maximal wall shear stress at the AVC is approximately 3 to 4 times lower in gata1 mutants ( S10 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…For the gata1 mutants, XYTZ images of the heart were captured at a frame rate of 100 frames per second for 80 frames, and the beating heart was realigned using BeatSync2.0 [ 79 ]. We track the ventricle volumes across time with a motion estimation algorithm [ 40 ] and calculate flow rates via the rate of volume changes of the ventricle. Subsequently, AVC shear rate is estimated with the assumption of a parabolic flow profile across a maximum inscribed circle in the cross section of the AVC, thus providing conservatively maximum wall shear rate values in the gata1 mutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Please note that in case of patients (e.g. arrhythmia) heart movements might be irregular mostly impacting cyclic periodicity [72] however smoothness assumption in a small local neighborhood should still hold based on findings from feasibility studies reported by Elen et al [10]. Moreover, in the preferred spatiotemporal regularization scheme (STBR-2), the spatial neighborhood size is always larger than temporal neighborhood size in our implementation thus ensuring that the algorithm is not biased by temporal information.…”
Section: Discussionmentioning
confidence: 97%
“…vmtk. org), and then a validated cardiac motion estimation algorithm (Wiputra et al 2020) was used to propagate the 3D reconstruction to all time points. Similar to previous work (Ho et al 2019b), the threshold values for segmentation were iteratively determined so that volumetric calculations from motion tracking would show minimum retrograde flow across the atrioventricular junction, which was a feature demonstrated in the literature for both normal and LAL embryos (Tobita and Keller 2000), and which we could verify with Doppler measurements in some embryos.…”
Section: Image Processingmentioning
confidence: 99%